(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Arterial hypertension remains one of the most prevalent cardiovascular disorders worldwide and a leading risk factor for morbidity and mortality. Despite the availability of multiple antihypertensive agents, a significant proportion of patients fail to achieve optimal blood pressure control, resulting in resistant hypertension. This condition poses serious clinical challenges and increases the risk of cardiovascular complications such as stroke, myocardial infarction, and heart failure. The present article aims to analyze the clinical causes of drug resistance in arterial hypertension and to evaluate modern individualized treatment strategies. Emphasis is placed on pathophysiological mechanisms, patient-related factors, and contemporary personalized therapeutic approaches that improve blood pressure control and clinical outcomes.